Research of changes of strength indicators of semi-rigid covers glued by modified adhesive compositions - Paliukh, Oleksandr; Kyrychok, Petro; Trishchuk, Ruslan; Korobka, Maxym (Technology audit and production reserves, 2020)
The object of research is the processes for producing modified adhesive compositions based on PVA (polyvinyl acetate) dispersions for use in technological processes for the manufacture of semi-rigid book and magazine covers. The conducted experimental studies are based on the application of a comparative method for determining the tensile strength of glued, without bias, samples of binding materials using modified adhesive compositions and identical compositions without modification. The main assumption of the study is that the use of polymer thickeners and emulsifiers compatible with latex PVA, which are actively used in the technological processes of the paper and printing industries, contribute to the formation of additional strength of semi-rigid covers. This can be achieved without analysis and the selection of possible components, taking into account the mechanical properties that arise after the use of such modifiers that substantially depend on the adhesive strength between the material of the outer part of the cover and the adhesive binder. It is proposed for an experimental study of the use of substances with high adhesive properties to thick coated papers and thin binding boards, from which semi-rigid book and magazine covers are made. The structural features of adhesive films obtained from polyvinyl acetate latex were determined, which have improved flexibility, elasticity, high adhesion and water resistance when water-soluble modifiers are added to them. An experimental determination was made of the possibilities of increasing the structural strength of semi-rigid book and magazine covers after gluing with modified binding adhesives, which did not significantly increase the thickness of the adhesive layer and did not change the contour geometry of the manufactured covers. It was proved that the adhesive mixtures used to modify the PVA dispersion did not affect the structural homogeneity of the glued spatial structure of the semi-rigid covers, and did not affect the appearance of external defects in the form of plane inhomogeneity, or point thickenings of the surface of the covers. The results of studies on the gluing of structural parts of reamers of semi-rigid covers with modified adhesive compositions create additional opportunities in planning the use of consumables in the manufacture of covers for strength indicators, predefined dimensional conditions for the use of modifier substances. Experimental studies have shown discreteness – growth, decrease in dimensional indicators of the strength of semi-rigid covers glued with modified adhesive compositions, contributes to the practical application of the results, both in the planning of technological processes and in the calculation of the cost of book production.